2018
DOI: 10.1111/jori.12260
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Insurance Deductible Demand Under Endogenous Premium Rates

Abstract: Government-subsidized insurance is ubiquitous, yet estimation of demand in such markets remains challenging. The premium charged for a given deductible is determined by actuarial construction; thus, observed choicepairs are endogenous leading to biased estimation under standard econometric approaches. A theoretical model and simulation study are developed, and a new identification strategy proposed. An empirical application using Federal Crop Insurance Program-a $100 billion/year program-data reveals that dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…However, some recent results go in an opposite way. Given that subsidy rates vary with coverage level, Woodard (2016) and Woodard and Yi (2018) considered the presence of endogeneity in the estimation of crop insurance demand, providing evidences of elastic responses from US farmers.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…However, some recent results go in an opposite way. Given that subsidy rates vary with coverage level, Woodard (2016) and Woodard and Yi (2018) considered the presence of endogeneity in the estimation of crop insurance demand, providing evidences of elastic responses from US farmers.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The implication of this finding is that if premiums are too high, then adverse selection issues may be compounded and lead to a higher risk pool where the program may become unsustainable. In contrast, Woodard and Ying (2018) recently found that demand may be more elastic when accounting for the endogeneity associated with premium rate calculations and participation 2…”
Section: Literature Reviewmentioning
confidence: 95%
“…Enrollees tend to assume larger risks which could increase the probability of loss associated with insured peril because the enrollee knows the insurance firm will definitely incur cost. Following Schlesinger (1985), Jack & Ormiston (1999), Tse (2009), Thogersen (2016), Woodard & Yi (2018) and Ogungbenle, et al (2020), the two types of payments payable by the insurance firm are (i) the payment per loss and (ii) payment per payment. The payment per loss random variable represents the losses over which payment is effected and losses on which payment is less than the agreed deductible.…”
Section: A Survey Of Casualty Preliminariesmentioning
confidence: 99%